GSM BASED SECURITY SYSTEM USING MICROCONTROLLER (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Security and automation is a prime concern in our dayto- day life. Everyone wants to be as much as secure as possible .Due to the inefficient system security problems are increases. Manual operated system may not be give hundred percent security. GSM based security system is fully automized and efficient syst, designed with the help of Microcontroller. In this system various types of alert signals are generated by the system, given to the owner as well as another person or system like police on their cell phones. With the help of this system we gets alert signal on our mobile phone. So this system reduces mainly efforts to carry any another object for getting an alert signals. This process is take the action with in the fraction of the second. We needs security at every place like Bank at home or apartment and also at office cabin ,shops, farms, parkingetc. With the help of GSM module system is transmit the alert signals to the owner. This system is applicable at every place where we need more security with the help of this system we can easily Find out who is entered in secure zone. With the help of CCTV camera system. This system is avoid extra use of energy using atomization.